WASTEWATER TREATMENT OF NPK FERTILIZER INDUSTRY USING SEQUENCING BATCH REACTOR AND GRANULAR ACTIVATED CARBON - Azalia, Amelinda Thomasina; Hendrasarie, Novirina (Journal of Environmental Engineering and Sustainable Technology, 2022)
contains COD, TSS, PO4, and Total-N pollutants that can contaminate water bodies if the treatment process is not carried out first. In this study, the NPK fertilizer industry waste treatment was carried out using sequencing batch reactors (SBR) and granular activated carbon (GAC) by adding the coagulation-flocculation process as a pre-treatment so that wastewater can meet the established quality standards. In this study, the reactors were operated at HRT 12, 24, and 48 hours using a GAC mass concentration of 0.5, 1, and 2 g/L. The results show the highest reduction of COD parameters by 67%, TSS by 82%, PO4 by 45%, Total-N by 76%, optimal HRT by 48 hours, and an optimal GAC mass concentration of 2 g/L. The aeration rate is operated at 14 L/min, with a PAC concentration of 3 g/L being optimal.